Integrative multiplatform molecular profiling of benign prostatic hyperplasia identifies distinct subtypes - Deli Liu (Nature Portfolio, 2020)
Benign prostatic hyperplasia (BPH) is one of the most common diseases affecting aging men with limited therapeutic options. In this study, the authors describe the molecular characterization of BPH performing genomic, transcriptomic and epigenetic analysis of 18 BPH cases.